Consolidation of country schools - Munger, Edna A. (My University, 1908)
Introduction: Any one who studies at all carefully the situation in our public schools today, will see that a change is imperative. The country school child has the same rights in regard to schooling as his city cousin. Yet, if we compare the two systems we will see that the country child does not have these equal privileges.
Citation: Munger, Edna A. Consolidation of country schools. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Education; Teaching; Schools; Graduating theses; Senior theses; Theses